Formação de professores e desenvolvimento profissional na educação de jovens e adultos - Maraschin, Mariglei Severo (2006)
This dissertation presents an action-research lived by the researcher and a group of teachers from YAE (initial years) from the Public State System of Santa Maria. The research sought, from the viewpoint of the action-research, the contribution of helpful works to the professional development of these teachers. The study group was consisted of active teachers from YAE, which they put themselves up to learn collaborativately and share knowledge and experiences, promoting a critical reflection built on theorical references, about their practice. The teacher s preparation in YAE deserves a special look, for it s increasing the number of schools that offer this category and the teacher s preparation courses didn t have in its curriculum subjects that would lead the teacher to think about the learning and teaching of young and adult students. Up against this reality it becomes fundamental to find continuous alternatives of how to prepare this teacher, which without this initial information he is challenged to work with YAE. The action-research constitutes a possibility of a continuous preparation because it promotes a collaborative learning among all subjects and the reflection of pedagogical practice. Therefore, based on the action-research, the group of teachers gathered twice a month to plan and put it into action. Through reflection, moment in which were built problematical issues about the work put into action, it was possible to produce knowledge concerning the preparation of teachers and about young and adult education. The voluntary group motivated the professional development of the teachers which had reported that they had been undertaking new attitudes as: a split in the old-fashioned way of teaching, personal development, the belief in the possibility of a change, the up bringing of new knowledge, the creation of an innovator work, a study commitment and courage to spread new pedagogical work in YAE. The experience demonstrated the importance of preparation courses for teachers to place in their resumé subjects which deal with the young-adult students, excluded from school; the university s necessity of approaching the school s routine and the school s organization, in a collaborative way, to prepare the teachers, to offer improvements and to encourage some positive change in the system.